Undo what is done to l. l has w added and the sum multiplied by 2, so divide by 2 and subtract w:
... l = P/2 -w
We know that m ║ n.
Let's first find the value 'x'.
When two lines are parallel, and a transversal is drawn, the angles on the same side of the transversal are equivalent.
This means that (5x + 16)° and (7x + 4)° are equivalent.
Equating them,
5x + 16 = 7x + 4
16 - 4 = 7x - 5x
12 = 2x
x = 12/2
x = 6°
Since we know the value of 'x', let's substitute them into the angles and find out the actual measurements.
5x + 16 = 5 × 6 + 16 = 30 + 16 = 46°.
7x + 4 = 7 × 6 + 4 = 42 + 4 = 46°.
Now let's find the value of 'y'.
If you observe carefully, (7x + 4)° and (y + 6)° form a linear pair.
This means that both those angles should add upto 180°.
Using that theory, the following equation can be framed:
(y + 6)°+ (7x + 4)° = 180°
Since we know the actual value of (7x + 4)°, let's substitute that value and move ahead.
(y + 6)° + 46° = 180°
y + 6 + 46° = 180
y + 52° = 180°
y = 180° - 52°
y = 128°
Therefore, the values of 'x' and 'y' are 46° and 128° respectively.
Hope it helps. :)
B² = 8b + 84
b² - 8b - 84 = 0
b = <u>-(-8) +/- √((8)² - 4(1)(-84))</u>
2(1)<u>
</u>b = <u>8 +/- √(64 + 336)</u>
2
b = <u>8 +/- √(400)
</u> 2<u>
</u>b = <u>8 +/- 20
</u> 2
b = 4 <u>+</u> 10
b = 4 + 10 b = 4 - 10
b = 14 b = -6
<u />
The solution to the given differential equation is yp=−14xcos(2x)
The characteristic equation for this differential equation is:
P(s)=s2+4
The roots of the characteristic equation are:
s=±2i
Therefore, the homogeneous solution is:
yh=c1sin(2x)+c2cos(2x)
Notice that the forcing function has the same angular frequency as the homogeneous solution. In this case, we have resonance. The particular solution will have the form:
yp=Axsin(2x)+Bxcos(2x)
If you take the second derivative of the equation above for yp , and then substitute that result, y′′p , along with equation for yp above, into the left-hand side of the original differential equation, and then simultaneously solve for the values of A and B that make the left-hand side of the differential equation equal to the forcing function on the right-hand side, sin(2x) , you will find:
A=0
B=−14
Therefore,
yp=−14xcos(2x)
For more information about differential equation, visit
brainly.com/question/18760518
Answer:2.26796
Step-by-step explanation: